Early ontogeny and sequence heterochronies in Leiuperinae (Athesphatanura: Leptodactylidae). - Grosso, Jimena Renee (2019)
The study of early development in Neotropical Leiuperinae frogs (Anura, Leptodactylidae) has been addressed by several works in recent times. However, a comparative develop- mental approach under a phylogenetic context was not available. Herein we analyzed the morphological and ontogenetic diversity of embryos belonging to 22 species of the three largest genera in Leiuperinae. We find that in most cases, variations fit with the phylogeny at the inter- and intrageneric levels. Embryo kyphosis and whitish color are synapomorphies for the clade grouping Physalaemus and Engystomops. The presence of a third lower tooth row on the oral disc is plesiomorphic for Leiuperinae, only changing in derived clades. The configurations and developmental trajectories of the lower lip are exceptionally diverse. The developmental sequences optimized on the phylogenetic tree recover an early differentiated first lower tooth row a synapomorphy of Pseudopaludicola and Physalaemus, and an early differentiated second row as synapomorphy of Pleurodema. On the other hand, few features are highly conserved in the subfamily, such as the adhesive glands universally present in a type-C configuration. Our results also suggest that the morphology and ontogeny of embryos is in some cases associated to the environment where they develop. A large body size, poorly developed transient respiratory structures, large yolk provision and delayed development of the digestive tract occur convergently in embryos inhabiting cold, oxygen- ated environments. Embryos that develop in warmer water bodies in xeric environments show more complex and persistent transient respiratory structures and an early onset of hind limbs development. Our survey highlights that morphology and early development of anurans can be a valuable source of information for phylogenetic studies, and provide fun- damental bases to explore and discuss how evolutionary changes can be shaped by envi- ronmental conditions.